Canon / Nurul Akmal Mohamed Ramli - Mohamed Ramli, Nurul Akmal (2022)
Canon is a global leader in photographic and digital imaging solutions. In this company analysis, it is focusing on digital imaging solution which is printer produced by the Canon to be investigate, identified, and analyzed along with their current problems and come out with solutions. The first problem regarding their product is unable to determine how many copies can be printed by the left ink in the cartilages or ink compartments. The printer only blinks when the ink almost empty but still cannot guess how many copies of papers still can be printed afterwards. As for the next problem is the margin setup. Sometimes, it will pop up margin error whenever using custom margin which is the printer cannot read and print according to the customed margin. It is not the human error but the system itself that not setup advanced for the margin perspective. Aside from that, there are a few solutions to the problems primarily are doing some innovation and upgrades some features to overcome the problems. One feature can be innovated on the printer is one digital compartment that showing how many copies of papers that can be printed. It is starting with the maximum copies are 20 copies and below according to the ink left in the cartilages or ink compartments. Another way to show how many copies can be printed is when attaching the USB wire of printer to the laptops or computers, before printing, there will show the digit that showing how many copies that can be printed. Next solution is the upgrade of the system that can detect the customed margin whenever printing when using Microsoft. All the solutions are considered to improve the quality product of printer to be served to the users in order to make the users convenient when using the printer.